The Guidance of the Prophet in Wiping on the Patient - Qusai Abu Shareah; Kholud Al-husban (دراسات: علوم الشريعة والقانون, 2021)
The research aims to explain how Prophetic Sunnah concerning in humanity by explaining the guidance of the prophet peace be upon him in wiping on the patient to preserve the human’s health and safety. The study followed the inductive method by extrapolating the prophetic hadiths that highlight the Prophet's guidance in the subject of the patient wiping, collecting the statements of commentators, and following the scientific material in its sources and the analytical method by analyzing the relevant texts, appending them to the appropriate topics, and indicating the teachings that guide it for the benefit of the individual and society and The comparative approach through the comparison of the Prophet's guidance in establishing the rules of the survey on the patient, and the proven facts in modern medical science. The study came to the following conclusions. First, the definition of wiping and patient did not depart from the Ijtihad and sayings of the scholars, but that the Sunnah is rich in narrations related to these two terms. It also concluded that the totality of the narrations indicated that it is lawful to lay hands on the patient and that it is mustahabb to pray for him for recovery and well-being, so that Allah Almighty may heal the patient with the blessing of supplication. The study recommends the need to conduct more studies on the wiping on the patient, from an Islamic point of view, and seek to root it as a reliable science in medical care.